2003
DOI: 10.1076/neur.9.3.274.15563
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Atypical Antipsychotics with a Cognitive Enhancer (Donepezil) Improves Regional Brain Activity in Schizophrenia Patients: A Pilot Double-blind Placebo Controlled BOLD fMRI Study

Abstract: Cognitive impairments are cardinal features of schizophrenia and predictors of poor vocational and social outcome. Imaging studies with verbal fluency tasks (VFT) lead some to suggest that in schizophrenia, the combination of a failure to deactivate the left temporal lobe and a hypoactive frontal lobe reflects a functional disconnectivity between the left prefrontal cortex and temporal lobe. Others have theorized that an abnormal cingulate gyrus modulates such fronto-temporal connectivity. Thus addition of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Risch et al (2001) found increased activation of the prefrontal cortex and the basal ganglia, and improvements on cognitive assessments typically used to assess AD such as the Alzheimer's Disease Assessment Scale (ADAS). A second imaging study found increased activity of the left frontal lobe and cingulate and improvements on the Controlled Word Association Task (COWAT) (Nahas et al, 2003). Other studies have found improvements on select behavioral and cognitive assessments.…”
Section: Schizophreniamentioning
confidence: 93%
“…Risch et al (2001) found increased activation of the prefrontal cortex and the basal ganglia, and improvements on cognitive assessments typically used to assess AD such as the Alzheimer's Disease Assessment Scale (ADAS). A second imaging study found increased activity of the left frontal lobe and cingulate and improvements on the Controlled Word Association Task (COWAT) (Nahas et al, 2003). Other studies have found improvements on select behavioral and cognitive assessments.…”
Section: Schizophreniamentioning
confidence: 93%
“…128 Despite these moderate effects in clinical studies, the addition of donepezil resulted in an increase in left frontal lobe and cingulate activity in a functional magnetic resonance imaging study. 129 Moreover, the addition of donepezil to a stable antipsychotic regimen has been found to ameliorate signs of tardive dyskinesia. 130 In contrast to these studies, several other studies failed to find a beneficial effect of the adjunctive use of donepezil in schizophrenia.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 99%
“…One group found that donepezil normalized fMRI findings on a verbal fluency task (Nahas et al, 2003) and another group found that rivastigmine improved performance on a sustained attention task (Aasen et al, 2005).…”
Section: Despite Clear Effects Of Other Cholinergic Compounds Chomentioning
confidence: 99%